Interrelationship of Political Science with Other Social Sciences - Prasain, Indira Devi; Dhakal, Ram Prasad; Prasain, Pradip Sarma (NPRC Journal of Multidisciplinary Research, 2026)
Objective: The current study explores the nature of political science as a multidisciplinary subject based on literature review and research articles. Methodology: A qualitative and interpretive approach will be adopted, utilizing only theoretical knowledge and not conducting any data collection process. Findings: Political science draws upon several disciplines for its theory and methodology. History is connected with it to put politics in context; economics contributes to its analysis of policies and resources distribution; sociology sheds light on the role of society in political processes. Anthropology helps in analyzing the culture of governments, whereas psychology helps in understanding voter psychology and the nature of leaders. Public health offers knowledge about the involvement of governments during health emergencies, and demography is helpful for electoral strategies. Geography offers spatial analysis, including electoral geography, whereas cultural studies offer knowledge of how norms affect political systems. Additionally, political science involves analysis in the disciplines of international relations (international interactions and diplomacy), law (making laws and their effects), and public administration. Conclusion: Political science cannot be fully understood in a vacuum. Any comprehensive understanding of its political phenomena requires interdisciplinary analysis involving history, economics, sociology, anthropology, psychology, public health, demography, geography, cultural studies, international relations, law, and public administration